Recalibrating Indonesia’s Diplomacy in the Pacific: Strategic Engagement for Economic Cooperation and Sovereignty Safeguarding - Mada Kaka, Yulius (Politeia : Journal of Public Administration and Political Science and International Relations, 2026)
This article examines Indonesia’s diplomatic engagement with the Pacific nations in the context of geopolitical rivalry and economic opportunities. Indonesia has pursued development assistance, scholarships, cultural programs, and limited security cooperation, yet its diplomacy remains shaped by the issue of sovereignty concerning Papua. Using descriptive qualitative methods and policy analysis, the study explores how Indonesia’s Pacific engagement reflects what this paper terms The Pacific Paradox—the simultaneous pursuit of expansionary influence and defensive sovereignty. The findings show that initiatives remain fragmented and transactional, limiting Jakarta’s credibility compared to major powers. To address these challenges, Indonesia’s diplomacy to the region can be done by establishing a comprehensive regulatory framework for Pacific diplomacy; promoting buying missions to enhance economic linkages; and introducing a Generalized System of Preferences (GSP) scheme for selected countries. These strategies would strengthen Indonesia’s regional posture and foster long-term partnerships while safeguarding its national interests.